Analisis Kemampuan Penalaran Matematis Materi Pecahan Kelas III SDN Pati Kidul 01 - Umi Virgianti; Melinda Khoriyah Ningrum; Lovika Ardana Riswari (Universitas Muhammadiyah Kuningan, 2023)
This article analyzes problem-based mathematical reasoning abilities in third grade elementary school students with fraction material at Pati Kidul 01 Elementary School. This study aims to understand the level of students' mathematical reasoning problem ability in learning mathematics. The research method used was qualitative involving third grade elementary school students at Pati Kidul 01 Elementary School. The data was collected through a mathematical reasoning test and analyzed to interpret the results. The results of the data analysis provide insight into the strengths and weaknesses in understanding the material and the implications for students' learning mathematics. This study also makes comparisons with related studies to gain a more comprehensive understanding. This study provides important information for the development of third grade elementary school students' mathematics learning and provides recommendations to strengthen their mathematical reasoning abilities.